2021
DOI: 10.3897/pharmacia.68.e73158
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of the antidiabetic activities of sulphated polysaccharide extract from Caulerpa lentillifera

Abstract: Caulerpa lentillifera is a type of green seaweed that is cultivated in tropical and subtropical areas. The objectives of this study were to determine the characteristics of the sulfated polysaccharides from C. lentillifera and evaluate its antidiabetic activity. In the initial process of this study, samples were macerated with ethanol (1:10). Then, the maceration residue was extracted with an accumulator at 75 °C for three hours. The crude extract yield was 4.16% based on weight seaweed. Ion chromatography pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…C. lentillifera contains various bioactive molecules that can contribute to its anti-hyperglycemic activity, including sulfated polysaccharides and monosaccharides. A previous study by Fajriah et al showed that purified polysaccharides of C. lentillifera had significant inhibition capability against α-glucosidase ( 41 ). A -glucosidase is an enzyme located in the brush borders of the small intestine, which operates by cleaving disaccharides into glucose to be further absorbed ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…C. lentillifera contains various bioactive molecules that can contribute to its anti-hyperglycemic activity, including sulfated polysaccharides and monosaccharides. A previous study by Fajriah et al showed that purified polysaccharides of C. lentillifera had significant inhibition capability against α-glucosidase ( 41 ). A -glucosidase is an enzyme located in the brush borders of the small intestine, which operates by cleaving disaccharides into glucose to be further absorbed ( 42 ).…”
Section: Discussionmentioning
confidence: 99%